Pengaruh Variasi Konsentrasi Karaginan Kombinasi Emulgator Anionik dan Nonionik Terhadap Formulasi Losion Astaxanthin Ekstrak Minyak Cincalok - Nia Risnawati; Siti Nani Nurbaeti; Hadi Kurniawan (Jurnal Sains dan Kesehatan, 2021)
ABSTRACT Cincalok is a typical food of West Kalimantan, Indonesia. Cincalok is made from the fermentation of rebon shrimp, which contains astaxanthin compounds inside them. Astaxanthin has strong antioxidant properties with an IC50 value of 18.75 ppm. Astaxanthin from cincalok oil extract can be formulated into a lotion for skin care. Lotion were made in 4 formulas. Formula F1 and F2 used a combination of anionic emulgators (stearic acid and TEA), formulas F3 and F4 used a combination of nonionic emulgators (Span 60 and Tween 60). Concentration carrageenan as a viscosity agent was 0.75% in F1 and F3, and concentration of 1% in F2 and F4. All formulas were tested for their physical properties such as other organoleptic test, homogenity, spreadibility, adhesion, pH , viscosity, and globul size. Lotion were also tested for astaxanthin levels contained in lotion. The results showed that the formula F3 was the best formula based on physical properties and astaxanthin levels test in lotion. Keywords: Astaxanthin, Anionic, Cincalok, Lotion, Nonionic